2021
DOI: 10.1080/03670244.2021.1982711
|View full text |Cite
|
Sign up to set email alerts
|

“Everywhere You Look, You’ll Find Food”: Emerging Adult Perspectives Toward the Food Media Landscape

Abstract: This study explores what emerging adults value in food media, i.e. food-focused content and personae in media. Emerging adults (18-25) are an important target group for food media as they transition towards nutritional independence and consume media substantially. Seven semi-structured focus groups were conducted with thirty-seven Belgian participants. Thematic analysis revealed three themes (hedonism, ability, information) grouping nine subthemes (entertainment, sensory appeal, convenience, familiarity, cost,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 99 publications
0
18
0
Order By: Relevance
“…The motives for watching food-related content identified in this study were information acquisition, emotional satisfaction, and enjoyment. In previous studies on food content watching, the general watching motives were killing time, habitual viewing, entertainment, information acquisition, vicarious satisfaction, and personal relationship, all of which were related to the type of content [ 21 , 27 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motives for watching food-related content identified in this study were information acquisition, emotional satisfaction, and enjoyment. In previous studies on food content watching, the general watching motives were killing time, habitual viewing, entertainment, information acquisition, vicarious satisfaction, and personal relationship, all of which were related to the type of content [ 21 , 27 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the adolescents’ food content watching routes were YouTube and social media, and online platforms were mainly used. Adolescents used online platforms more frequently than TVs [ 26 , 41 ]. The unrefined online media exposure of adolescents had a significant impact on emotions such as physical dissatisfaction [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research has mainly focused on investigating how emerging adults perceive social media recipes (e.g. Wang et al, 2022), from which we can also deduce how recipes may contribute to food literacy (Decorte et al, 2022;Steils and Obaidalahe, 2020;Teunissen et al, 2023;Vaterlaus et al, 2015;Wang et al, 2022). Here, the research found that emerging adults perceive recipes on social media as an important source of education related to various food literacy components (i.e.…”
Section: References To Food Literacy Aspectsmentioning
confidence: 91%
“…Recipe-related content from food influencers is often visually attractive, presents the information in an easy-to-follow way and mentions ingredients that are affordable and accessible, which is extremely appealing for emerging adults (Decorte et al, 2022;Rogers et al, 2022). Furthermore, food influencers have been recognised as experts in successfully communicating about food and building relationships with younger audiences, given their ability to selectively choose content and communication techniques (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the data collection, ethical approval was granted by the Ethics Committee for the Social Sciences and Humanities of the University of Antwerp (Ref No: SHW_19_44). This paper is part of a larger project that aims to capture food media experiences and perceived influences on food-related behaviors among emerging adults (see also Decorte et al, 2022).…”
Section: Methodsmentioning
confidence: 99%